Erosion Mechanism of Cohesive River Bank and Bed of Soai Rap River (Ho Chi Minh City) - Vinh, Bui Trong; Ichiro, Deguchi (Vietnam Journal of Earth Sciences, 2012)
In recent years, river bank and bed erosion has been one of the most severe problems and caused much damage to economic-social activities and environment of Cuu Long and South-eastern regions. Soai Rap River (Ho Chi Minh City) has been chosen as main navigational channel for big ships with 70.000 DWT to Hiep Phuoc Port. Dredging up to 12m carried out will cause river bank unstably. High wave - induced by big ships has accelerated the erosion rate of this bank. In this paper, field investigations have been done to measure erosion rate of the river bank. Beside, the numerical models have been also applied to calculate the distribution of effective shear stresses caused by waves and currents. The results showed that erosion rates of cohesive bank materials are greater than those of cohesive bed materials from 2 to 10 times. These results indicate that local high waves approach to the banks are the main factor which causes erosion severely. Other factors such as the mixing rates of sand, silt and clay contents, moisture contents, salinity, dead roots and leaves, and aquatic caves and holes also affect the stability of the cohesive bed and bank strongly.